Abundance of fin whales in West Greenland in 2007 - Heide-Jørgensen, M. P.; Laidre, K. L.; Simon , M.; Burt, M. L.; Borchers, D. L.; Rasmussen, M. (J. Cetacean Res. Manage., 2023)
An aerial line transect survey of fin whales (Balaenoptera physalus) conducted off West Greenland in 2007 was used to estimate the current abundance of fin whales on the summer feeding ground. A total of 24 sightings of fin whale groups were collected during 8,632km of survey effort in sea states <5. Based on conventional distance sampling techniques an abundance of 4,359 whales (95% CI 1,879–10,114) was estimated. The survey was conducted as a double platform survey and mark recapture distance sampling techniques were used to correct for perception bias which resulted in an estimate of 4,468 whales (95% CI 1,343–14,871). Both estimates are negatively biased because no corrections were applied for whales that were submerged during the passage of the survey plane. The abundance estimate furthermore only represents the coastal areas of West Greenland. The sightings at the westernmost border of the strata suggest that the entire Baffin Bay-Davis Strait summer abundance of fin whales could be considerably larger. Based on comparison with previous surveys in West Greenland in 1987/88 and 2005 it appears that the fin whale abundance in West Greenland has increased.